Production of lipid and carbohydrate in tetradesmus obliquus UPSI-JRM02 under nitrogen stress condition - Norjan Yusof (Tanjung Malim, 2021)
Production of lipid and carbohydrate in tetradesmus obliquus UPSI-JRM02 under nitrogen stress condition by Norjan Yusof